Efektivitas Pembelajaran Qira’ah Berbasis Konstruktivisme Melalui Classpoint (Studi Eksperimen pada Siswa SMA As-Syafi’iyah 01 Jakarta) - Nafisa'ah, Salsabila; Mahyudin, Erta; Royani, Ahmad (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
This study aims to examine the effectiveness of qira’ah learning based on constructivist theory using the ClassPoint platform in improving students’ reading comprehension skills. The research problem is rooted in students' weaknesses in understanding Arabic texts and their low learning motivation, with an initial average score of 56. This study employed a quantitative approach with a quasi-experimental design involving 25 students in the experimental group using ClassPoint and 25 students in the control group with conventional methods. Data were collected through pre-tests and post-tests. The results show that the average pre-test score in the experimental group increased from 56 to 82.12 in the post-test. Statistical analysis confirmed that this improvement was significant, with a t-count of 5.15, which is higher than the t-table values at the 5% and 1% significance levels. Additionally, this learning model enhanced student engagement through discussions, presentations, and interactive quizzes. These findings demonstrate that the application of constructivist theory combined with interactive technology such as ClassPoint offers an innovative solution to overcome the limitations of conventional methods in teaching qira’ah.